2009
DOI: 10.4049/jimmunol.182.1.274
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Controls Regulatory T Cell Peripheral Homeostasis and Is Required for Suppression of Pancreatic Islet Autoimmunity

Abstract: The CTLA-4 pathway is recognized as a major immune inhibitory axis and is a key therapeutic target for augmenting antitumor immunity or curbing autoimmunity. CTLA-4-deficient mice provide the archetypal example of dysregulated immune homeostasis, developing lethal lymphoproliferation with multiorgan inflammation. In this study, we show that surprisingly these mice have an enlarged population of Foxp3+ regulatory T cells (Treg). The increase in Treg is associated with normal thymic output but enhanced prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
142
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 40 publications
12
142
0
Order By: Relevance
“…The most intuitive explanation is that this simply reflects widespread T-cell activation. However, these CD4 1 CD25 1 T cells all stain brightly for FOXP3 suggesting an expansion of Treg, which attempt unsuccessfully to control the ensuing lymphoproliferation and autoimmunity [63]. Recently, using antibody blockade, CTLA-4 has been shown to regulate Treg numbers and homeostasis in intact mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…The most intuitive explanation is that this simply reflects widespread T-cell activation. However, these CD4 1 CD25 1 T cells all stain brightly for FOXP3 suggesting an expansion of Treg, which attempt unsuccessfully to control the ensuing lymphoproliferation and autoimmunity [63]. Recently, using antibody blockade, CTLA-4 has been shown to regulate Treg numbers and homeostasis in intact mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, its role in Treg development and homeostasis is less well defined. CTLA-4 does not appear to be obligatory for Treg generation because these cells are present in CTLA-4 KO mice (46) and are even found at increased numbers (47), suggesting it may be providing a negative feedback signal to maintain Treg homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent observation associated with anti-CTLA-4-mediated tumour rejection had been a positive shift in the intra-tumoural ratio of Teff to T reg . A number of studies had demonstrated that anti-CTLA-4-mediated expansion of both Teff and T reg in the blood and secondary lymphoid organs of mice [34][35][36]. It was therefore unclear how anti-CTLA-4 mAb act to preferentially expand Teff in the tumour whilst simultaneously expanding both populations in the periphery.…”
Section: Ctla-4 Therapymentioning
confidence: 99%